Qingxin Kaiqiao Fang Inhibits Aβ25-35-Induced Apoptosis in Primary Cultured Rat Hippocampal Neuronal Cells via the p38 MAPK Pathway: An Experimental Validation and Network Pharmacology Study. (4th August 2020) - Wang, Tian-Qi; Lai, Xiao-Xiao; Xu, Lu-Ting; Shen, Yan; Lin, Jian-Wei; Gao, Shi-Yu; Hu, Hai-Yan
Abstract : Qingxin kaiqiao fang (QKF), a traditional Chinese medicine compound, has been applied to treat Alzheimer's disease (AD) for many years and has exhibited remarkable effects. However, the underlying mechanism is still not explicit. The current study aims to investigate whether QKF exerts an antiapoptotic role through the p38 MAPK pathway in the course of AD. Network pharmacology analysis was applied to study the effective components, possible therapeutic targets, and AD-related pathway of QKF. Further, the AD cell model was established using amyloid-beta (A β )25-35 peptide and primary hippocampal neuronal cells extracted from newborn Sprague-Dawley rats. Microtubule-associated protein-2 (MAP-2) imaging was used to detect the morphology of hippocampal neurons. Western blot (WB) analysis was applied to detect the protein expression levels of p38 MAPK, p-p38 MAPK, Bcl-2, Bax, caspase-3, and cleaved caspase-3. Cell viability and apoptosis were determined using cell counting kit-8 (CCK-8) and terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) assays, respectively. SB203580 and U46619 were used to detect changes in cell morphology, cell viability, and apoptosis upon inhibiting or activating p38 MAPK. Our present work showed that QKF protects hippocampal neuronal morphology, enhances cell viability, and reduces the number of TUNEL-positive cells. In addition, our results showed that QKF increased the expression levels of antiapoptotic proteins and decreased the expression of proapoptotic proteins. QKF at 25 mg·mL −1 best inhibited neuronal apoptosis among the three doses of QKF by suppressing p38 MAPK activity. Collectively, QKF plays an antiapoptotic role via the p38 MAPK pathway.